Legal Responsibility of Financial Institutions in Money Market Transactions - Lase, Apriaman; Elizaberth, Citra; Napitupulu, Diana R.W. (Universitas Islam Negeri Sumatera Utara, 2025)
The money market plays a strategic role in the financial system, particularly in providing liquidity for economic actors. However, in practice, money market transactions are not free from various legal risks that may impact financial stability. Financial institutions, as key players in money market transactions, have a legal responsibility to ensure compliance with regulations and to provide protection for the parties involved. This study aims to analyze the legal responsibility of financial institutions in money market transactions and their legal implications for the national financial system. Using a normative research method with a statutory and conceptual approach, this study explores the various regulations governing money market transactions and the legal protection mechanisms for related parties. The findings indicate that compliance with regulations is a crucial factor in preventing legal risks, where strengthening supervision and implementing the prudential principle are essential aspects of maintaining money market stability. Therefore, policy harmonization and increased transparency in money market transactions are necessary to ensure a safer, fairer, and more sustainable financial system.